ICT-based fluorescent ratiometric probe for monitoring mitochondrial peroxynitrite in living cells. (5th July 2021) - Du, Yuting; Wang, Hongliang; Zhang, Ting; Wei, Wen; Guo, Minmin
Abstract : Mitochondria-targeted near-infrared fluorescent probe for the detection of peroxynitrite and the bioimaging of peroxynitrite in cells. Abstract : Peroxynitrite (ONOO − ) is a reactive oxygen species (ROS) that causes serious damage to living cells and is the cause of a series of human diseases. It is reported that mitochondria are the major site of ONOO − production. Therefore, accurate and rapid detection of intracellular ONOO − is important in pathological processes. Herein, a mitochondria-targeted ratiometric fluorescent probe (DMANI ) has been rationally designed based on the coumarin–hemicyanine hybrid framework by regulating the intramolecular charge transfer (ICT) effect. The DMANI can capture ONOO − at low concentrations via direct addition with the CC bond to give an obvious fluorescent signal change from red to blue based on the ICT process. The possible mechanism for this electrophilic addition process was confirmed using electrospray ionization mass spectrometry (ESI-MS) and 1 H-NMR spectra. DMANI exhibited a good selectivity, a large Stokes shift (248 nm), a low detection limit (40 nM), and a rapid response (within 20 s) to ONOO − . More importantly, DMANI was successfully used for ratiometric imaging and monitoring of the fluctuations of mitochondrial ONOO − in living cells.